To solve the equation \((x + 9)^2 = 1\) using the square root property, follow these steps:
-
Apply the square root: Take the square root of both sides of the equation: \[ x + 9 = \pm \sqrt{1} \]
-
Calculate the square root: \(\sqrt{1} = 1\), so we have: \[ x + 9 = 1 \quad \text{or} \quad x + 9 = -1 \]
-
Solve for \(x\):
-
For the first equation: \[ x + 9 = 1 \quad \Rightarrow \quad x = 1 - 9 \quad \Rightarrow \quad x = -8 \]
-
For the second equation: \[ x + 9 = -1 \quad \Rightarrow \quad x = -1 - 9 \quad \Rightarrow \quad x = -10 \]
-
-
Final Solutions: The solutions to the equation \((x + 9)^2 = 1\) are: \[ x = -8, -10 \]
So your final answer is: \[ -8, -10 \]